The influence of financial literacy and attitude towards financial behaviour amongst undergraduate students: a cross-country evidence - Khalisharani, Hanin; Johan, Irni Rahmayani; Sabri, Mohamad Fazli (Universiti Putra Malaysia, 2022)
Undergraduate students should be able to manage their finances wisely while they are living apart from their parents. Therefore, good financial literacy and attitude should be developed during college to instil positive financial behaviour. It is a cross-country study to analyse the influence of financial literacy and attitude toward financial behaviour amongst Indonesian and Malaysian undergraduate students. This research involved 204 students from the Faculty of Human Ecology, IPB University, Indonesia, and Universiti Putra Malaysia. Data were collected through a self-report questionnaire with a convenience sampling technique. In general, the results revealed that the student’s level of financial literacy was recorded as moderate, while financial attitude and behaviour were categorised as poor. This study identified that Indonesian students scored higher in financial literacy, whereas Malaysian students recorded better financial attitude and behaviour scores. Multiple regression results showed that financial attitude had a significant positive effect on financial behaviour amongst Indonesian and Malaysian students and the group. In contrast, financial literacy had a negative effect on financial behaviour amongst the respondents, except in Malaysia. Moreover, students’ characteristics, such as age, grade point average (GPA), and income, had no significant impact on financial behaviour. The presence of financial education and socialisation to enhance financial behaviour are needed not only to focus on cognitive areas but also to encourage a positive attitude. Stronger support and regulation from the government and stakeholders are vital to ensure the programme’s success.